Pengaruh Bimbingan Kelompok Dengan Teknik Self Management Terhadap Kedisiplinan Belajar Siswa Kelas XII IPS Di SMA Negeri 1 Ketanggungan Brebes - M. Taufik Hidayat; Siti Fitriana; M.A. Primaningrum Dian (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The research is motivated by several problems of undisciplined behavior in learning, namely: (1) some students are still late for coming to school; (2) some students still cheat, often skip classes, are noisy in class, and are late in collecting assignments from the teacher; and (3) some students did not do homework from the teacher. The aim of the study was to determine the effect of group guidance using self-management techniques on the learning discipline of class XII IPS students at SMA Negeri 1 Keuntungan Brebes. The study used a quantitative approach with Pre-Experimental Designs of the One Group Pretest-Posttest Design type. The population of this study were all students of class XII IPS at SMA Negeri 1 Keuntungan Brebes totaling 72 students, consisting of class XII IPS 1 totaling 36 students and class XII IPS 3 totaling 36 students. The research sample was students of class XII IPS 1 SMA Negeri 1 Keuntungan Brebes, totaling 36 students. The sampling technique uses a purposive sampling technique. The data collection technique is a non-test with a psychological scale. Data analysis techniques using descriptive statistics. Test the hypothesis using paired samples t-test. The results showed that there was an effect of group guidance using self-management techniques on the learning discipline of class XII IPS 1 students at SMA Negeri 1 Keuntungan Brebes. The magnitude of the effect is indicated by the difference in the mean pre-test and post-test, that is, the mean pre-test is 80.53 to the mean post-test is 84.89, so an average increase is obtained. mean of 4.361 or 4%. It can be concluded that there is an influence of group guidance with self-management techniques on the learning discipline of class XII IPS students at SMA Negeri 1 Keuntungan Brebes.